Clinical and Laboratory Characteristics of Patients with Mono and Coinfection of Dengue and Scrub typhus - Banstola, Hemanta; Shrestha, Tirtha Man; Bhattarai, Dipesh; Ghimire, Manoj; Chhetri, Surendra Bahadur (Journal of Nepal Health Research Council, 2023)
Background: Dengue is a neglected tropical disease, and Scrub typhus is an emerging tropical illness in Nepal. Coinfection between them is found in literature and clinical practice. The objective of this study is to describe and compare the demographic, clinical, and laboratory characteristics of patients with mono and coinfection of Dengue and Scrub typhus. Methods: This was a single-center hospital-based retrospective study, performed at Beni District Hospital, Nepal. The patient who was diagnosed with mono and coinfection of Dengue and Scrub typhus from 1st January 2020 to 16th September 2020 were included. Data regarding demographic characteristics, symptoms, signs, and laboratory parameters were collected and analyzed. Results: In 53 patients who fall under the inclusion criteria of our study, 12 patients had coinfection with dengue and Scrub typhus with headache being the most common symptom regardless of mono or coinfection followed by myalgia and arthralgia. Total platelet counts at the time of admission were lower in the coinfection group with increasing thrombocytopenia during the disease course in comparison to mono-infection. The maximum temperature recorded, elevation in hepatic enzymes, and duration of defervescence were more in the coinfection group in comparison to dengue and scrub mono-infection. Conclusions: Mono and coinfection of Dengue, Scrub typhus present with common clinical symptoms, laboratory findings. With limited resources for screening and diagnosis, clinical prediction based on symptoms alone or together with lab parameters is difficult which is further difficult in the presence of Co-infection. Keywords: Clinical; coinfection; dengue; laboratory parameter; scrub typhus